On social psychopathology: Example with German justice. (13th April 2021) - Michailov, M.; Neu, E.; Welscher, U.; Gerdzhikov, A.; Foltinova, J.; Foltin, V.; Holler, M.; Weber, G.
Abstract : Introduction: INTRODUCTION-OBJECTIVES. Similar to philosophy (regina-scientiarum) is psychiatry fundamental-discipline for all-medical&social sciences. Immanuel KANT: Primus inter pares of ARISTOTELES&PLATON considered over 200years ago physiological and pragmatic anthropology-[1]. Social physiology is given-[3-4]. Consideration of social-psychopathology in German-justice-[2]. Objectives: REFERENCES. [1]-Kant, I: BdXI, 371-393, BdXII, 399, 625-638:Suhrkamp-TB-Wiss. [2]-Neu, E/Michailov, M.Ch/Welscher, U/et-al.: 2a.-FISP-2018-Beijing/Philos (1348-50, 1373-4, 1420); 2013-Athens Abstr.Book(AB):464-5/503-4/766; 2008-Seoul-ProcVol.4: 101-108/195-214/229-237; 2003-Istanbul:273-281; IVR-2019-Luzern (Law), Progr-Book p.116. 2b.-EPA-2020-Madrid, Eur.Psychiatry 63S, EPP0834/5+EPV0581/1470; EPA-2019-Warsaw, 56S, S689; EPA-2018-Nice, 48/S1, S623&567&662. 2c.-WPA-2021-Bangkok (in-press). 2019-Lisbon, E-Poster WCP19-2137/-1822/-1839. 2018-Mexico-City, Abs.-Book WCP18-0584/-0625/-0643/-0654. 2011-Buenos-Aires, AB:PO1.200. [3]-Glasachev, O: Sechenov Physiol.J 80/no5, 1994, p.139-143 (Russian), ref. in English. [4]-Seeley, T.D: Social-Physiology Honey-Bee, Book-1996. Methods: [5]-Daily-journal-"tz"-München, esp. every Tuesday 2016-2019: reports on Res.-Houses, e.g. 14.02.2019, 15.02.17, 06.12.16/p.10, 18.10.16/p.10, 17.11.2020/p.6. Süddt.Zeitung-München no172/p.30, 2017. Mü.-Merkur:16.11.2020/p.32; 19.11.2020/p.29. FAZ:20.10.2019/p.53; 16.11.2020/p.21. BUROW, P: Justiz am Abgrund&Ein Richter klagt an. GNISA, J, Präs.-Dt.Richterverein: „Ende der Gerechtigkeit", Herder-2017. SCHLEIF, T/Amtsrichter: Buch „Urteil: ungerecht", zeit-online 24.10.2019. Hans-Jochen&Liselotte VOGEL:„Mehr Gerechtigkeit", 2019 „Wohn-Irrsinn"(Enteignungen). ZANTKE, S (Richter-Amtsgericht-Zwickau): TV-Programm„Auf einen Blick" Nr.47, 2018, S.24. [6]-Luetge, Ch et-al.(ed): Experimental-Ethics, Palgrave-Macmillan 2014. [7]-Pegoraro, R/Vatican: «Arzt&Christ» 38:3-55, 1992. Results: RESULTS Prominent German experts for justice: Patrick BUROW, Jens GNISA/President Law-Association/Germany, Torsten SCHLEIF/Amtsrichter, Hans-Jochen VOGEL/Ex-Minister, Stephan ZANTKE/Richter reflect in their books fundamental-criticism of German justice [5]. Inst.-Ecol.-Med./IUM investigated psychopathology of juridical-offices&law-court in Munich (Amtsgericht). Analysis suggests presence of symptoms for pseudologia-phantastica, psychopathy, cyclophrenia (esp.mania), etc. conc. observations on many persons (n>30). Conclusions: CONCLUSION. Juridical situation in Germany demonstrates contradiction to human-rights (EU-CHARTA, art.1-8/25-26/33-35), ignoring moral-philosophy, related to human obligations/I.Kant-[1], experimental ethics/Ch.Luetge et-al.-[6], medical personnel/R.Pegoraro-[7]. Only paradigm change in law-policy incl. enlarged implication of moral philosophy-theology, psychiatry-psychology, social philosophy in juridical eduction & practices could counteract disastrous juridical situation in Germany and on global level, supporting UNO-AGENDA21 for better education-health-ecology-economy (see 2.). Disclosure: No significant relationships.